2020
DOI: 10.34172/mejdd.2020.177
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Effect of Aloe Vera Gel on Acetic Acid-Induced Ulcerative Colitis in Rat

Abstract: BACKGROUND The use of herbal and synthetic compounds can be effective in improving the areas and repair of tissues that have been affected during the processes like what happens in ulcerative colitis (UC) as a common inflammatory disorder. According to the beneficial effects of aloe vera, in this study, we aimed to assess the therapeutic effects of oral aloe vera gel on acetic acid-induced colitis in rats by histopathological and molecular analysis of Bax, and BCL-2 genes expression (using RT-PCR technique) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In addition to human studies, there are many in vivo studies on use of MSCs in treatment of UC in animal models. Various animals have been used as experimental model of UC and treatment of disease with MSCs including mouse in 39 studies 4,20 , rat in 13 investigations 4,21 , Guinea pig in one study 4,22 and dog in one study 23 . In our research, rat model has similarly been used for induction of colitis and AdSCs as a therapeutic approach with successful results of healing in colonic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to human studies, there are many in vivo studies on use of MSCs in treatment of UC in animal models. Various animals have been used as experimental model of UC and treatment of disease with MSCs including mouse in 39 studies 4,20 , rat in 13 investigations 4,21 , Guinea pig in one study 4,22 and dog in one study 23 . In our research, rat model has similarly been used for induction of colitis and AdSCs as a therapeutic approach with successful results of healing in colonic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs have been used by several researchers in the treatment of experimental colitis using various animal models, including mice, rats, and Guinea pigs (Table 4). In these animals, some researchers have used trinitrobenzene sulfonic acid (TNBS) to induce colitis [37,[65][66][67][68], while several studies reported the use of dextran sulfate sodium (DSS) to induce colitis models [47,48,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] and many authors applied acetic acid to induce colitis [1,3,4] (Table 4). The first BMSCs transplantation was conducted in 2006 in a TNBS-induced colitis mice model, revealing the important role of cell therapy in the repair of injured intestinal mucosa, as well as the downregulation of immune function of T cells [65].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%
“…Dynamic interactions between the gastrointestinal epithelium and the mucosal immune system result in intestinal homeostasis and optimal immunosurveillance, but a destabilization in these interactions among predisposed people can lead to development of chronic inflammatory diseases called inflammatory bowel disease (IBD), which mainly covers Crohn's disease (CD) and ulcerative colitis (UC) [1]. UC affects the rectum and may involve any part of the colon in a continuous pattern, whereas CD can affect any part of the gastrointestinal tract [2].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the healing effect of the aqueous leaf extract of Aloe vera in an animal model of experimentally induced colitis was investigated. The favorable effects confirmed through the significant reduction in Bax mRNA expression and elevation in Bcl-2 mRNA expression when compared with the colitis group without treatment [ 25 ]. In another study, 50 and 300 mg/kg of Aloe vera gel extract were used to evaluate the improvement in the symptoms of UC in rats.…”
Section: Introductionmentioning
confidence: 99%